The Pangkalpinang District Court Decision: An Analysis of the Criminal Offense of Collecting Personal Data Without Permission - Editho Berilphizaldi; Husni Thamrin (GoAcademica Research & Publishing, 2026)
This study aims to analyze the application of Article 67 of Law No. 27 of 2022 on Personal Data Protection in cases of unauthorized collection and use of personal data for activating prepaid cards, as outlined in the decision of the Pangkalpinang District Court. The research identifies how the panel of judges assessed the defendant's actions in collecting personal data without consent and whether such actions violated the constitutional rights of the data subjects. Additionally, this study examines the roles and responsibilities of corporations and individuas involved in this case, and the legal consequences, both material and immaterial, for the personal data subjects. The findings of the study indicate that the criminal act of collecting personal data without permission can cause harm to individuas, highlighting the need for strict law enforcement to protect privacy rights in the digital age.